PERBANDINGAN EFEKTIFITAS TEKNIK RELAKSASI DAN TEKNIK DISTRAKSi TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN FRAKTUR - Evatamia H. Holo (CHMK Applied Science Journal, 2018)
Fracture usually caused by trauma or physical exertion. Fracture causing common symptom of pain. Pain is an uncomfortable, subjective feeling where only the sufferer can feel it. Almost all pain felt by patients with fracture will be treated with analgesic, but many patients and doctors are less satisfied with long-term administration. This situation encourages the development of nonpharmacological techniques to treat pain such as relaxation and distraction techniques. The purpose of this study was to determine the effectiveness of relaxation technique and distraction technique to reduce the intensity of pain in patients fracture in the Surgery Ward of RSUD Prof. Dr. W. Z. Johannes Kupang. The research method was Pre Experiment with One Group Pretest-Postest design, the selection of sample using Accidental Sampling. Sample of 18 respondents. This research was conducted on 9 February until 16 March 2017 in the Surgery Ward of RSUD Prof. Dr. W. Z. Johannes Kupang. Data collection was done by giving relaxation technique (deep breath) and distraction technique (listening to music), then the researchers measure the scale of the respondent pain using Hayward pain scale. The results used independent t showed that the relaxation technique was more effective in reducing the pain of fracture patients than the distraction technique with pain reduction mean = 2.00 > 1.67. Conclusion, relaxation techniques and distraction techniques are able to reduce the intensity of pain and there was a comparison of pain intensity of fracture patients after relaxation technique and distraction technique. Keywords: Pain, Relaxation Technique, Distraction Technique